2022
DOI: 10.21203/rs.3.rs-2095091/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening and identification of potato StSPS1, a potential crucial gene regulating seed potato vigor

Abstract: Backrounds Sucrose phosphate synthase (SPS), as a vital rate-limiting enzyme catalyzing the synthesis of sucrose precursors, plays an indispensable role in the regulation of seed potato vigor. However, the genes encoding SPS in potato have not been fully analyzed, and the main genes affecting seed potato vigor have not been screened and identified. Methods and results In this study, four members of the StSPS family were identified with the potato genome database by homologous gene and conserved domain compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Tuber dormancy is a complex physiological process that developed as an adaptation strategy to cope with stressful environments [ 3 ]. The match between tuber dormancy time and storage, planting, and shelf periods poses a significant challenge to dormancy control, and improper sprouting is a constant concern for the potato industry [ 4 ]. Recent studies have found several key genes that play roles in the maintenance of dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…Tuber dormancy is a complex physiological process that developed as an adaptation strategy to cope with stressful environments [ 3 ]. The match between tuber dormancy time and storage, planting, and shelf periods poses a significant challenge to dormancy control, and improper sprouting is a constant concern for the potato industry [ 4 ]. Recent studies have found several key genes that play roles in the maintenance of dormancy.…”
Section: Introductionmentioning
confidence: 99%